Mitigation of land-related crimes by the integrated team for the prevention and eradication of land mafia in Palangka Raya - Sosanta, Theo Onesiforus; Wardhani, Novea Elysa; Kristanto, Kiki (Journal of Law Science, 2025)
The mitigation of land-related crimes in Palangka Raya has become a serious challenge due to the increasing prevalence of land mafia practices, which harm the public and hinder legal certainty. To address this issue, the government established the Integrated Team for the Prevention and Eradication of Land Mafia, consisting of various agencies, including the police, the prosecutor's office, the National Land Agency (BPN), and local government authorities. This team plays a crucial role in preventing, uncovering, and taking action against various land mafia schemes, such as document forgery, land encroachment, and illegal land transactions. This study aims to analyze the effectiveness of the integrated team's efforts in handling land-related crimes and to identify the challenges faced in policy implementation. Using an empirical approach, the study finds that although the integrated team has successfully uncovered several land-related cases, various challenges remain, including limited inter-agency coordination, weak law enforcement, and a lack of public awareness regarding their legal rights to land. Data was collected through interviews, direct observation, and documentation studies. Therefore, a more comprehensive strategy is needed, including regulatory strengthening, capacity-building for law enforcement officers, and public education, to create a transparent and equitable land governance system in Palangka Raya.